ANALISIS PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PRODUKTIVITAS PENJUALAN (Studi Pada Langsung Enak Bakery Sumbawa Besar) - A Asmini; Supri Wahyudi; Binar Dwiyanto Pamungkas (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to analyze the factors of production on sales productivity at Langsung Enak Bakery in 2017-2021. This type of research is associate research, namely research that aims to determine the relationship between two or more variables. The variables to be examined are labor and raw material variables as independent variables (X) and sales productivity variables as the dependent variable (Y). The data used is quantitative data in the form of the number of workers, the cost of raw materials and the number of sales for the last five years, namely 2017-2021, which were obtained from documents and archives contained in the Langsung Enak Bakery company at Sumbawa Besar. The data that has been collected will then be processed using the SPSS program to be studied using techniques which include simple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that labor and raw materials have a positive and significant effect on sales productivity at Langsung Enak Bakery Sumbawa Besar, both partially and simultaneously. The degree of influence of labor and raw materials on sales productivity at Langsung Enak Bakery Sumbawa Besar is 93.6%, while the remaining 6.4% is influenced by other variables outside this research model, such as product quality, price, location, promotion and others.